Economic component in the causes and consequences of emergencies - Trush, Oleksandr Olehovych; Gorovyi, Dmytro Anatoliiovych (Дніпровський національний університет імені Олеся Гончара, 2018)
Purpose – to elucidate the "economic nature" of an emergencies, to expand the list of reasons for the formation and consequences of the emergencies, taking into account the economic component, and to provide a description of their interrelation in this process. Design/Method/Approach. This work evaluates and summarizes studies that provide economic characteristics and assess the causes and consequences of a emergencies. Findings. An analysis of previous studies on emergencies pointed to a limited focus on economic issues associated. In this paper, the authors substantiated the feasibility and proposed to highlight the economic component in the management of prevention of emergencies, in the management of minimizing negative consequences and to consider this component in the classification of types of emergencies. This work focuses on the causal link between economic costs for the prevention, elimination and elimination of the effects of emergencies (economic losses) in the emergency management system. The examples have proved that all of the emergency preceding processes are economical, that emergency actions are limited to an economic factor, and that emergency situations can have economic consequences. An economic component can be both a cause and a consequence of an emergency. At the same time, the economic causes of emergencies directly affect only the economic consequences (inflation-impoverishment of the population), and their impact on the remaining consequences - indirect, due to the impact of other factors-consequences. Theoretical implications. This research identifies a new classification group "economic circumstances" in the classification of types of emergencies for the causes of the emergence and spheres of manifestation of the consequences. Practical implications. The isolation and systematization of the economic component of emergencies allows us to take into account the economic factor in the development of appropriate prevention algorithms, actions in emergencies or actions to eliminate the negative effects of these events. Originality/Value. The originality of the work is to illustrate the connection between the cause of emergencies and each of its manifestations with the help of the fan matrix. This approach has allowed a clearer outline and a clear indication of the causal relationship in the processes associated with the emergency situation. For example, a causal relationship with the types of emergencies based on the economic component is illustrated with the aid of a fan matrix. Research limitations/Future research. This research is the basis for further improvement of approaches to the estimation of economic indicators of emergencies taking into account the proposed classification groups of types of emergencies. Paper type – theoretical.

Мета роботи – з'ясувати "економічну природу" надзвичайних ситуацій (НС), з урахуванням економічної складової розширити перелік причин формування та наслідків НС, описати їх взаємозв'язки у цьому процесі. Дизайн/Метод/Підхід дослідження. Оцінка та узагальнення досліджень, які надають економічні характеристики та оцінюють причини та наслідки НС. Результати дослідження. Аналіз попередніх досліджень з питань НС вказав на обмежене зосередження на економічних питаннях. У даній роботі обґрунтовано доцільність і запропоновано виділити економічну складову в управлінні запобіганням НС, в управлінні мінімізацією негативних наслідків НС і розглянути цей компонент в класифікації видів НС. Зосереджено увагу на причинно-наслідковому зв'язку між економічними витратами на запобігання, ліквідацію та усунення наслідків НС (економічних втрат) в системі управління НС. На прикладах доведено, що економічний характер мають усі процеси, що передують НС, що дії під час НС обмежені економічним чинником, а також що НС можуть мати економічні наслідки прояву. Економічна компонента може бути як причиною, так і наслідком НС. Разом з тим, економічні причини НС прямо впливають лише на економічні наслідки (інфляція –зубожіння населення), а їх вплив на решту наслідків –побічний, через вплив решти факторів-наслідків. Теоретичне значення дослідження. Виокремлено нову класифікаційну групу «економічні обставини» в класифікації видів НС за причинами виникнення та сферами прояву наслідків. Практичне значення дослідження. Виокремлення та системататизація економічної компоненти НС дозволяє враховувати економічний чинник під час розробки відповідних алгоритмів запобігання, дій під час НС або дій з усунення негативних наслідків цих подій. Оригінальність/Цінність/Наукова новизна дослідження. Зв’язок між причиною НС і кожним її проявом проілюстровано за допомогою віялової матриці. Такий підхід дозволив більш чітко окреслити та наочно показати причинно-наслідковий взаємозв’язок у процесах, пов’язаних з надзвичайною ситуацією. Для прикладу за допомогою віялової матриці проілюстровано причинно-наслідковий зв’язок типами НС з урахуванням економічної компоненти. Обмеження дослідження/Перспективи подальших досліджень. Це дослідження є основою для подальшого удосконалення підходів до оцінки економічних показників НС з урахуванням запропонованих класифікаційних груп типів НС. Тип статті – теоретична.
Економічна компонента в причинах і наслідках надзвичайних ситуацій
Keywords: classification; fan matrix; causal relationship; expenses for overcoming of consequences; insurance; management; класифікація; віялова матриця; причинно-наслідковий взаємозв’язок; витрати на подолання наслідків; страхування; управління